Improvement Axial Dispersion Calculation in Fibrous Garnished Fixed Beds Using the Neural Method - Hassani, Djamel; Didi, Faouzi; Hanini, Salah; Daoud, Kamel (International Journal of Membrane Science and Technology, 2023)
To determine accurately the physical modeling of flow through porous media and / or in chemical reactors, especially in the field of low Reynolds numbers, it is essential to compute the coefficient of axial dispersion. In prior studies, we employed the neural method to compute axial dispersion within fixed beds with parallelepiped and spherical packings. In the present study we apply the same method of calculation on heterogeneous fixed beds with large anisotropy using data from Poirier and Trinh on fibrous beds. Such an investigation could be however very useful while one has the desire to predict the mixing process to characterize the axial dispersion in fixed beds of anisotropic particles and when experimental measurements are not accessible and / or difficult to implement as for reactors and / or industrial complex porous media. To show also the robustness and applicability of this method, the calculation results obtained will be modeled using expressions similar to those proposed by Poirier and Trinh, so that we can compare our results with those obtained by these authors, under the same operating conditions. Furthermore, our study offers a comprehensive analysis encompassing all three examined fixed bed configurations, namely parallelepiped, spherical, and fibrous arrangements.